Dynamics of arbuscular mycorrhizal fungi in the rhizosphere soils of safflower from certain areas of Telangana - BHUMI NARASIMHA REDDY*, HINDUMATHI AMBALLA and (Indian Phytopathology, 2016)
The rhizosphere soil samples of safflower from cultivated agricultural fields in different areas of Telangana were surveyed for study arbuscular mycorrhizal fungal association. The results obtained showed that safflower is arbuscular mycorrhizal (AM) fungal dependant. The soil physico-chemical factors of safflower soils supported good AMF spore population and favoured high AM fungal species community. The AM fungal species isolated from the present soils exhibited the association of 42 species distinguished on the basis of morphological criteria representing 6 genera, Acaulospora, Glomus, Gigaspora, Scutellospora, Funneliformis and Entrophospora. The genus Glomus represented by 16 species formed the predominant genus, Acaulosporare presented by 13 species, Gigaspora and Funneliformis by 3 species each, Scutellospora by 4 spp., Entrophospora by two species and one genus/species was unidentified.